A high nitrogen content porous carbon dioxide adsorption material and its preparation method and application

By preparing nitrogen-containing porous carbon/silicon adsorbent, the problem of insufficient adsorption capacity and stability of solid porous materials is solved, and high-efficiency, low-consumption carbon dioxide adsorption performance and good cycle stability are achieved, which is suitable for large-scale carbon dioxide capture.

CN118287042BActive Publication Date: 2024-12-13CNOOC GAS & POWER GRP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410385461.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-01
Publication Date
2024-12-13
Estimated Expiration
2044-04-01

AI Technical Summary

Technical Problem

In the existing carbon dioxide capture technology, solid porous materials have low adsorption capacity and poor stability of carbon dioxide gas, which limits high-efficiency and low-consumption carbon dioxide adsorption and capture.

Method used

Using the preparation method of nitrogen-containing porous carbon dioxide adsorption materials, the in-situ polymerization of template agents, zinc-containing inorganic salts, melamine and formaldehyde can generate porous carbon/silicon adsorbents with high nitrogen content, and the pore structure is formed by pyrolysis to improve the Adsorption performance and cycle stability.

Benefits of technology

The prepared adsorbent has a high nitrogen content and a large specific surface area. It has good adsorption performance on carbon dioxide, good circulation stability, and can maintain an adsorption capacity of more than 95% in a low-concentration carbon dioxide environment. It is suitable for large-scale carbon dioxide capture.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The present invention discloses a porous carbon dioxide adsorbent material with high nitrogen content and a preparation method and application thereof. The preparation method of the carbon dioxide adsorbent material of the present invention comprises the following steps: (1) dissolving a template in water, adding mesitylene and a zinc-containing inorganic salt to obtain a solution A; (2) adding melamine, a formaldehyde aqueous solution and an inorganic base into water, heating to react, and obtaining a solution B; (3) mixing the solution A and the solution B, adding a hydrochloric acid aqueous solution and a silicon source, and collecting a precipitate; (4) drying the precipitate and then pyrolyzing it at 900 to 1100° C. to carbonize and volatilize zinc to form a porous structure, and obtaining the carbon dioxide adsorbent material. The material of the present invention has high nitrogen content and specific surface area, and has good CO2 adsorption performance and cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of carbon dioxide adsorption and capture, and specifically relates to a high-nitrogen porous carbon dioxide adsorption material and a preparation method and application thereof. Background Art

[0002] In recent years, various natural problems such as global warming, glacier melting, and sea level rise caused by the greenhouse effect have begun to become more and more numerous. Among them, carbon dioxide is the dominant gas of the greenhouse effect. The main source of carbon dioxide emissions is the combustion of fossil fuels such as coal, oil, and natural gas in industrial production. Although green energy and renewable energy are developing rapidly, there is still a long way to go before they can be widely used. In order to effectively slow down the intensification of the greenhouse effect, it is necessary to develop efficient and economical methods to capture the emitted carbon dioxide.

[0003] At present, the carbon dioxide capture and separation technologies that have been successfully applied mainly include chemical absorption, membrane separation and adsorption. Among them, the alkanolamine compound used in the absorption method is monoethanolamine, which has a fast absorption rate and a relatively mature process. It is widely used in industrial processes such as oil refining and synthetic ammonia. However, the amine compound absorption method has high regeneration energy consumption and serious corrosion to the equipment. The membrane separation method uses the difference in permeability of different gases to a film made of polymer materials to separate gases. The membrane separation method has a simple device, but it is generally difficult to achieve large-scale carbon capture. In comparison, the adsorption method usually has simple equipment, easy operation, low energy consumption, low cost, no corrosion and pollution, and is conducive to large-scale application. Therefore, the use of adsorption technology for carbon dioxide capture has great application prospects, and the key is the development of high-performance absorbents.

[0004] Some common solid porous materials, such as porous carbon materials, molecular sieves, alumina, silica gel, metal organic framework materials and membrane materials, can be used to remove carbon dioxide from gases. However, most of the above materials have low adsorption capacity for carbon dioxide gas. Although some porous adsorption materials loaded with organic amines have the advantages of high adsorption capacity and good selectivity, they also have problems such as poor stability, which greatly limits the efficient and low-cost carbon dioxide adsorption capture. Summary of the invention

[0005] The purpose of the present invention is to provide a high nitrogen content porous carbon dioxide adsorption material and its preparation method and application. The prepared adsorbent has high nitrogen content and specific surface area, good CO2 adsorption performance and good cycle stability.

[0006] In a first aspect, the present invention provides a method for preparing a carbon dioxide adsorbent material, comprising the following steps:

[0007] (1) dissolving the template in water, adding mesitylene and a zinc-containing inorganic salt to obtain a solution A;

[0008] (2) adding melamine, formaldehyde aqueous solution and inorganic base into water and heating to react to obtain solution B;

[0009] (3) mixing the solution A and the solution B, adding a hydrochloric acid aqueous solution and a silicon source, and collecting the precipitate;

[0010] (4) After drying the precipitate, pyrolyzing it at 900-1100° C. to carbonize it and volatilize zinc to form a porous structure, thereby obtaining the carbon dioxide adsorbent material.

[0011] The technical concept of the present invention is as follows: the present invention in-situ polymerizes a nitrogen-containing carbon source (such as melamine) and formaldehyde to generate a polymer precursor, which is then mixed with a template agent and a zinc-containing inorganic salt, and a silicon source is added to form a skeleton structure, and further carbonized at 900-1100°C, and the zinc element volatilizes to form a large number of pore structures to obtain a porous carbon / silicon adsorbent. The prepared adsorbent has high nitrogen content and specific surface area, good CO2 adsorption performance, and good cycle stability.

[0012] In the above preparation method, the template is Pluronic F127 or P123; wherein Pluronic F-127 is also known as Poloxamer 407, that is, Polyethylene-polypropylene glycol, which is a polyoxyethylene polyoxypropylene ether triblock copolymer, and its Chinese name is poloxamer, polyether or polyoxyethylene polyoxypropylene, and its molecular formula is H(C2H4O) x (C3H6O) y (C2H4O) z OH, molecular weight is about 12.6kD, melting point is about 56℃, CAS Number 9003-11-6; P123 is a triblock copolymer, the full name is polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (PEO-PPO-PEO);

[0013] The zinc-containing inorganic salt is zinc nitrate, zinc chloride or zinc acetate;

[0014] The molar ratio of the template, the mesitylene and the zinc-containing inorganic salt is (2-1):(2-1):1, such as 2:2:1, 1:1:1, 1:2:1 or 2:1:1;

[0015] In step (1), the molar ratio of the template to the water is 1:(10-20), such as 1:10, 1:20 or 1:15.

[0016] In the above preparation method, in step (2), the molar ratio of the melamine, the formaldehyde in the formaldehyde aqueous solution, the inorganic base and the water is 10:10:(1-2):(3-5), such as 10:10:1:3, 10:10:2:5, 10:10:2:3 or 10:10:1:5;

[0017] The inorganic base is a metal hydroxide, such as sodium hydroxide or potassium hydroxide;

[0018] The mass concentration of the formaldehyde aqueous solution is 30% to 40%, such as 30%, 35% or 40%;

[0019] The heating temperature is 80-100° C., such as 80° C., 90° C. or 100° C., and the heating time is 0.5-2 h, such as 0.5 h, 2 h, 1 h, 1.5 h.

[0020] In the above preparation method, the silicon source is tetraethyl orthosilicate or silica sol.

[0021] In the above preparation method, the volume ratio of the solution A to the solution B is 1:(3-5), such as 1:3, 1:4 or 1:5;

[0022] The volume ratio of the hydrochloric acid aqueous solution, the silicon source and the solution B is 3:2:40;

[0023] The mass concentration of the hydrochloric acid aqueous solution is 37%;

[0024] When the silicon source is silica sol, the silicon dioxide content of the silica sol is 30% to 40%, such as 30%, 40%, or 35%, and the diameter of the silicon dioxide in the silica sol is 100 to 200 nm, such as 100 nm or 200 nm.

[0025] In the above-mentioned preparation method, the pyrolysis is carried out in an inert atmosphere, such as nitrogen or argon;

[0026] The heating rate of the pyrolysis is 1 to 10°C / min, such as 5°C / min;

[0027] The pyrolysis temperature is 900-1100° C., such as 900° C. or 1100° C.; the pyrolysis time is 2-4 hours, such as 2 hours, 3 hours or 4 hours.

[0028] In the above-mentioned preparation method, the carbon dioxide adsorption material is a nitrogen-containing porous carbon / silicon-based material.

[0029] Further, the N content of the carbon dioxide adsorbent material is >10%, such as 12.27wt%;

[0030] The specific surface area of ​​the carbon dioxide adsorbent material is 400 to 500 m 2 / g, such as 460m2 / g.

[0031] In a second aspect, the present invention provides a carbon dioxide adsorption material prepared by any of the methods described above.

[0032] In a third aspect, the present invention provides use of the carbon dioxide adsorption material in capturing carbon dioxide in gas.

[0033] In the above application, the capture temperature may specifically be 0°C.

[0034] In the above application, the volume percentage of carbon dioxide in the gas may specifically be 5%.

[0035] In the above application, the gas may specifically be industrial flue gas.

[0036] Compared with the prior art, the present invention has the following beneficial effects:

[0037] (1) The nitrogen content of the adsorbent is high>10%;

[0038] (2) The specific surface area of ​​the adsorbent can reach 400-500m 2 / g;

[0039] (3) The carbon dioxide adsorption capacity of the adsorbent can reach more than 3 mmol / g;

[0040] (4) The adsorbent has stable performance, is easy to separate and regenerate, and has good recycling performance. Experiments have found that after five cycles of low-concentration carbon dioxide (5%) at 0°C, the adsorption capacity can still be maintained above 95%. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 is the X-ray diffraction pattern of the product of Example 1;

[0042] Figure 2 is a scanning electron microscope image of the product of Example 2;

[0043] Figure 3 is a nitrogen adsorption-desorption curve diagram of the product of Example 4;

[0044] Figure 4 is the isothermal adsorption curve of carbon dioxide for the products of Examples 2, 4, 6 and 7 at 0°C;

[0045] Figure 5 This is a graph showing the results of the cyclic adsorption test of carbon dioxide on the products of Examples 2, 4, 6 and 7 at 0°C. DETAILED DESCRIPTION

[0046] The present invention is further described in detail below in conjunction with specific embodiments, and the examples provided are only for illustrating the present invention, rather than for limiting the scope of the present invention. The examples provided below can be used as a guide for further improvements by those of ordinary skill in the art, and do not constitute a limitation of the present invention in any way.

[0047] The methods used in the following examples, unless otherwise specified, are all conventional methods, carried out according to the techniques or conditions described in the literature in the art or according to the product instructions. The materials, reagents, etc. used in the following examples, unless otherwise specified, can all be obtained from commercial sources.

[0048] Example 1: Preparation of porous carbon / silicon-based carbon dioxide adsorption material with high nitrogen doping content

[0049] Specifically prepared according to the following steps:

[0050] (1) dissolving the template agent Pluronic F127 in deionized water, adding mesitylene and zinc nitrate, wherein the molar ratio of the template agent, mesitylene and zinc nitrate is 2:2:1, and the molar ratio of the template agent to water is 1:10, to obtain solution A;

[0051] (2) adding melamine, formaldehyde aqueous solution (30 wt%) and NaOH into deionized water, wherein the molar ratio of melamine, formaldehyde, NaOH and deionized water is 10:10:1:3, and reacting at 80° C. for 0.5 h to form solution B;

[0052] (3) mixing solutions A and B, wherein the volume ratio of solutions A and B is 1:3, adding a hydrochloric acid aqueous solution (37 wt%) and tetraethyl orthosilicate, wherein the volume ratio of the hydrochloric acid aqueous solution, tetraethyl orthosilicate and solution B is 3:2:40, and obtaining a precipitate;

[0053] (4) The precipitate was filtered, dried, and pyrolyzed in a nitrogen atmosphere at 900° C. for 2 hours at a heating rate of 5° C. / min to obtain a porous carbon / silicon-based carbon dioxide adsorption material with a high nitrogen doping content.

[0054] Example 2: Preparation of porous carbon / silicon-based carbon dioxide adsorption material with high nitrogen doping content

[0055] Specifically prepared according to the following steps:

[0056] (1) dissolving the template agent Pluronic F127 in deionized water, adding mesitylene and zinc nitrate, wherein the molar ratio of the template agent, mesitylene and zinc nitrate is 1:1:1, and the molar ratio of the template agent to water is 1:20, to obtain solution A;

[0057] (2) adding melamine, formaldehyde aqueous solution (40 wt%) and NaOH into deionized water, wherein the molar ratio of melamine, formaldehyde, NaOH and deionized water is 10:10:2:5, and reacting at 100° C. for 2 h to form solution B;

[0058] (3) mixing solutions A and B, wherein the volume ratio of solutions A and B is 1:4, adding a hydrochloric acid aqueous solution (37 wt%) and tetraethyl orthosilicate, wherein the volume ratio of the hydrochloric acid aqueous solution, tetraethyl orthosilicate and solution B is 3:2:40, and obtaining a precipitate;

[0059] (4) The precipitate was filtered, dried, and pyrolyzed in a nitrogen atmosphere at 1100° C. for 4 hours at a heating rate of 5° C. / min to obtain a porous carbon / silicon-based carbon dioxide adsorption material with a high nitrogen doping content.

[0060] Example 3: Preparation of porous carbon / silicon-based carbon dioxide adsorption material with high nitrogen doping content

[0061] Specifically prepared according to the following steps:

[0062] (1) Dissolving the template agent P123 in deionized water, adding mesitylene and zinc chloride, wherein the molar ratio of the template agent, mesitylene and zinc chloride is 2:2:1, and the molar ratio of the template agent to water is 1:10, to obtain solution A;

[0063] (2) adding melamine, formaldehyde aqueous solution (35 wt%) and NaOH into deionized water, wherein the molar ratio of melamine, formaldehyde, NaOH and deionized water is 10:10:1:3, and reacting at 80° C. for 1 h to form solution B;

[0064] (3) mixing solutions A and B, wherein the volume ratio of solutions A and B is 1:5, adding a hydrochloric acid aqueous solution (37 wt%) and tetraethyl orthosilicate, wherein the volume ratio of the hydrochloric acid aqueous solution, tetraethyl orthosilicate and solution B is 3:2:40, and obtaining a precipitate;

[0065] (4) The precipitate was filtered, dried, and pyrolyzed in a nitrogen atmosphere at 900° C. for 2 hours at a heating rate of 5° C. / min to obtain a porous carbon / silicon-based carbon dioxide adsorption material with a high nitrogen doping content.

[0066] Example 4: Preparation of porous carbon / silicon-based carbon dioxide adsorption material with high nitrogen doping content

[0067] Specifically prepared according to the following steps:

[0068] (1) dissolving the template agent P123 in deionized water, adding mesitylene and zinc chloride, wherein the molar ratio of the template agent, mesitylene and zinc chloride is 1:1:1, and the molar ratio of the template agent to water is 1:20, to obtain solution A;

[0069] (2) adding melamine, formaldehyde aqueous solution (35 wt%) and NaOH into deionized water, wherein the molar ratio of melamine, formaldehyde, NaOH and deionized water is 10:10:2:5, and reacting at 100° C. for 1.5 h to form solution B;

[0070] (3) mixing solutions A and B, wherein the volume ratio of solutions A and B is 1:4, adding a hydrochloric acid aqueous solution (37 wt%) and tetraethyl orthosilicate, wherein the volume ratio of the hydrochloric acid aqueous solution, tetraethyl orthosilicate and solution B is 3:2:40, and obtaining a precipitate;

[0071] (4) The precipitate was filtered, dried, and pyrolyzed in a nitrogen atmosphere at 1100° C. for 4 hours at a heating rate of 5° C. / min to obtain a porous carbon / silicon-based carbon dioxide adsorption material with a high nitrogen doping content.

[0072] Example 5: Preparation of porous carbon / silicon-based carbon dioxide adsorption material with high nitrogen doping content

[0073] Specifically prepared according to the following steps:

[0074] (1) Dissolving the template agent P123 in deionized water, adding mesitylene and zinc acetate, wherein the molar ratio of the template agent, mesitylene and zinc acetate is 2:2:1, and the molar ratio of the template agent to water is 1:10, to obtain solution A;

[0075] (2) adding melamine, formaldehyde aqueous solution (40 wt%) and NaOH into deionized water, wherein the molar ratio of melamine, formaldehyde, NaOH and deionized water is 10:10:1:3, and reacting at 80° C. for 2 h to form solution B;

[0076] (3) mixing solutions A and B in a volume ratio of 1:4, adding hydrochloric acid aqueous solution (37 wt%) and silica sol (silicon dioxide mass content of 30%, silica diameter of ∼100 nm, hydrochloric acid aqueous solution, silica sol and solution B in a volume ratio of 3:2:40, and obtaining a precipitate;

[0077] (4) The precipitate was filtered, dried, and pyrolyzed in a nitrogen atmosphere at 900° C. for 2 hours at a heating rate of 5° C. / min to obtain a porous carbon / silicon-based carbon dioxide adsorption material with a high nitrogen doping content.

[0078] Example 6: Preparation of porous carbon / silicon-based carbon dioxide adsorption material with high nitrogen doping content

[0079] Specifically prepared according to the following steps:

[0080] (1) dissolving the template agent Pluronic F127 in deionized water, adding mesitylene and zinc acetate, wherein the molar ratio of the template agent, mesitylene and zinc acetate is 2:1:1, and the molar ratio of the template agent to water is 1:15, to obtain solution A;

[0081] (2) adding melamine, formaldehyde aqueous solution (35 wt%) and NaOH into deionized water, wherein the molar ratio of melamine, formaldehyde, NaOH and deionized water is 10:10:2:3, and reacting at 90° C. for 2 h to form solution B;

[0082] (3) mixing solutions A and B in a volume ratio of 1:3, adding hydrochloric acid aqueous solution (37 wt%) and silica sol (silicon dioxide mass content of 40%, silica diameter of ∼200 nm), and the volume ratio of hydrochloric acid aqueous solution, silicon source and solution B is 3:2:40, to obtain a precipitate;

[0083] (4) The precipitate was filtered, dried, and pyrolyzed in a nitrogen atmosphere at 900° C. for 3 hours at a heating rate of 5° C. / min to obtain a porous carbon / silicon-based carbon dioxide adsorption material with a high nitrogen doping content.

[0084] Example 7: Preparation of porous carbon / silicon-based carbon dioxide adsorption material with high nitrogen doping content

[0085] Specifically prepared according to the following steps:

[0086] (1) Dissolving the template agent P123 in deionized water, adding mesitylene and zinc nitrate, wherein the molar ratio of the template agent, mesitylene and zinc acetate is 1:2:1, and the molar ratio of the template agent to water is 1:15, to obtain solution A;

[0087] (2) adding melamine, formaldehyde aqueous solution (40 wt%) and NaOH into deionized water, wherein the molar ratio of melamine, formaldehyde, NaOH and deionized water is 10:10:1:5, and reacting at 90° C. for 0.5 h to form solution B;

[0088] (3) mixing solutions A and B in a volume ratio of 1:5, adding hydrochloric acid aqueous solution (37 wt%) and silica sol (silicon dioxide content of 35%, silica diameter of ∼200 nm), and the volume ratio of hydrochloric acid aqueous solution, silicon source and solution B is 3:2:40, to obtain a precipitate;

[0089] (4) The precipitate is filtered, dried, and pyrolyzed at 1100° C. for 3 hours to obtain a porous carbon / silicon-based carbon dioxide adsorption material with a high nitrogen doping content.

[0090] The properties of the porous adsorption material prepared by the present invention are as follows:

[0091] Figure 1 This is the X-ray diffraction diagram of the product of Example 1; a peak appears at about 20 degrees, which is a characteristic peak of carbon materials, indicating that the synthesized material is a carbon-containing material.

[0092] Figure 2 This is a scanning electron microscope image of the product of Example 2 at 30,000 times magnification; it can be seen from the image that the synthesized adsorption material is composed of fine particles and has a porous structure.

[0093] The surface nitrogen content of the sample of Example 3 was tested by using an energy dispersive spectrometer (EDS, Quantax200 XFLash6|60), and the nitrogen content was 12.27 wt %.

[0094] Figure 3 The graph is a nitrogen absorption-desorption curve of the product of Example 4; the upper curve is the desorption curve, and the lower curve is the adsorption curve. It can be seen from the figure that the nitrogen adsorption amount of the prepared adsorbent increases with the increase of relative pressure, and the surface area is about 460m 2 / g.

[0095] At 0°C, CO2 gas is brought into contact with the sample material at different pressures, the adsorption amount of CO2 is measured, and the isothermal adsorption curve of CO2 adsorbed by the sample material is plotted. Figure 4 The isothermal adsorption curves of carbon dioxide for the samples of Examples 2, 4, 6, and 7 at 0°C are shown. Under 1 atm, the adsorption amounts of the samples of Examples 2, 4, 6, and 7 are 3.07, 3.29, 3.13, and 3.11 mmol / g, respectively. At 0°C, low concentration carbon dioxide (5%, air) was brought into contact with the sample material, and the adsorption amount of CO2 at different cycle times was measured to draw a cyclic adsorption performance curve. Figure 5 The cyclic adsorption performance of low concentration carbon dioxide (5%) at 0°C for Examples 2, 4, 6, and 7 shows that the adsorption capacity can still be maintained above 95% after 5 cycles.

[0096] The present invention has been described in detail above. For those skilled in the art, without departing from the purpose and scope of the present invention, can implement the present invention in a wider range under equivalent parameters, concentrations and conditions. Although the present invention provides specific embodiments, it should be understood that the present invention can be further improved. In a word, according to the principle of the present invention, the application is intended to include any changes, uses or improvements to the present invention, including departing from the disclosed scope in the application and the changes made with conventional techniques known in the art.

Claims

1. A method for preparing a carbon dioxide adsorbent material, comprising the following steps: (1) dissolving the template in water, adding mesitylene and a zinc-containing inorganic salt to obtain a solution A; The template is PluronicF127 or P123; (2) adding melamine, formaldehyde aqueous solution and inorganic base into water and heating to react to obtain solution B; (3) mixing the solution A and the solution B, adding a hydrochloric acid aqueous solution and a silicon source, and collecting the precipitate; The silicon source is tetraethyl orthosilicate or silica sol; (4) After drying the precipitate, pyrolyzing it at 900-1100° C. to carbonize it and volatilize zinc to form a porous structure, thereby obtaining the carbon dioxide adsorbent material.

2. The preparation method according to claim 1, Features: The zinc-containing inorganic salt is zinc nitrate, zinc chloride or zinc acetate; The molar ratio of the template, the mesitylene and the zinc-containing inorganic salt is (2-1): (2-1): 1; In step (1), the molar ratio of the template to the water is 1:(10-20).

3. The preparation method according to any one of claims 1 to 2, Features: In step (2), the molar ratio of the melamine, the formaldehyde in the formaldehyde aqueous solution, the inorganic base and the water is 10:10:(1-2):(3-5); The inorganic base is sodium hydroxide or potassium hydroxide; The mass concentration of the formaldehyde aqueous solution is 30% to 40%; The heating temperature is 80-100° C. and the heating time is 0.5-2 h.

4. The preparation method according to any one of claims 1 to 2, Features: The volume ratio of the solution A to the solution B is 1:(3-5); The volume ratio of the hydrochloric acid aqueous solution, the silicon source and the solution B is 3:2:40; The mass concentration of the hydrochloric acid aqueous solution is 37%; When the silicon source is silica sol, the mass concentration of the silica sol is 30% to 40%, and the diameter of silicon dioxide in the silica sol is 100 to 200 nm.

5. The preparation method according to any one of claims 1 to 2, Features: The pyrolysis is carried out in an inert atmosphere; The heating rate of the pyrolysis is 1 to 10°C / min; The duration of the pyrolysis is 2 to 4 hours.

6. The preparation method according to any one of claims 1 to 2, Features: The carbon dioxide adsorption material is a nitrogen-containing porous carbon / silicon-based material.

7. The preparation method according to claim 6, Features: The N content of the carbon dioxide adsorbent material is >10%; The specific surface area of ​​the carbon dioxide adsorbent material is 400 to 500 m 2 / g.

8. The carbon dioxide adsorbent material prepared by the method according to any one of claims 1 to 7.

9. Use of the carbon dioxide adsorbent material according to claim 8 in capturing carbon dioxide in gas.

Citation Information

Patent Citations

  • Method for preparing high-surface-area nitrogenous mesoporous carbon material

    CN101823705A

  • Particle nanometer micropore material and preparing method thereof

    CN109821517A

  • Porous polymer material

    US20130189175A1